An empirical examination of benefits, challenges, and critical success factors of industry 4.0 in manufacturing and service sector. (November 2021) - Sony, Michael; Antony, Jiju; Mc Dermott, Olivia; Garza-Reyes, Jose Arturo
Abstract: Industry 4.0 marks a new paradigm and has expanded its domain from theoretical concepts to real-world applications. Industry 4.0 is, however, still in the state of infancy and conceptual state wherein it is not clear as to how to incorporate many dynamic technological concepts in different sectors. Previous studies have conceptually delineated the benefits, challenges, and CSFs of Industry 4.0, however, there is yet to be an empirical study that critically examines the differences in benefits, challenges, and critical success factors (CSFs) of Industry 4.0 in both manufacturing and service industries and rank them. This study through an online survey captures the view of senior management professionals who have experience in Industry 4.0 implementation in major companies in Asia, Europe, and North America. 96 senior management professionals participated in this study through an online survey. The qualitative data on benefits and challenges were analysed using thematic analyses. The quantitative data on critical success factors were ranked using the normalisation of the mean to find the most important factors. Further agreement analysis was conducted in the manufacturing and service sectors for the CSFs. This study identifies the top five benefits and challenges in the manufacturing and service industries. The CSFs for Industry 4.0 was put forward and ranked in both the manufacturing and service industries. Highlights: Empirical study on critical differences on sector wise benefits & challenges of Industry 4.0. Empirical sector wise analysis of critical success factors of Industry 4.0 Sector wise ranking of critical success factors of Industry 4.0 Top five benefits and challenges of Industry 4.0 implementation.